Can a Christ child have Down syndrome?. Issue 2 (13th May 2021) - Skotko, Brian G.
Abstract: Virgin and Child, a painting attributed to a follower of Andrea Mantegna completed around 1460, is currently in storage at the Museum of Fine Arts in Boston. With special supervised permission, I have visited the painting three times to assess whether this Christ child might have Down syndrome. My conclusion evolved each time—as did my appreciation for the synergy between physicians and art historians.